Vowel intelligibility in children with cochlear implants: An acoustic and articulatory study. (October 2017) - Turgeon, Christine; Trudeau-Fisette, Pamela; Fitzpatrick, Elizabeth; Ménard, Lucie
Abstract: In child cochlear implant (CI) users, early implantation generally results in highly intelligible speech. However, for some children developing a high level of speech intelligibility may be problematic. Studies of speech production in CI users have principally been based on perceptual judgment and acoustic measures. Articulatory measures, such as those collected using ultrasound provide the opportunity to more precisely evaluate what makes child CI users more intelligible. This study investigates speech production and intelligibility in children with CI using acoustic and articulatory measures. Ten children with unilateral or bilateral CIs and 13 children with normal hearing (NH) participated in the study. Participants repeated five English vowels (/a/, /e/, /i/, /o/, /u/) with and without auditory feedback. Ultrasound was used to capture tongue positions and acoustic signals were recorded simultaneously. The results showed that, despite quite similar acoustic results, the two speaker groups made different use of the tongue to implement vowel contrasts. Indeed, the tongue position was lower in the feedback OFF condition than the feedback ON condition for all participants, but the magnitude of this difference was larger for CI users than for their NH peers. This difference led to diminished intelligibility scores for CI users. This study shows the limitation of acoustic measurements alone and demonstrates how the use of articulatory measurements can explain intelligibility patterns. Moreover, our results show that when cochlear implantation occurs early in life and auditory feedback is available, CI users' intelligibility is comparable to that of their NH peers.